Dampak Masa Pandemi Covid-19 Pada Eksistensi Festival Film: Studi Kasus Festival Film Pelajar Jogja 2020 - Deddy Setyawan; Sri Rochana Widyastutieningrum; Handriyotopo Handriyotopo; Denny Antyo Hartanto; Febfi Setyawati (Institut Seni Indonesia Yogyakarta, 2025)
The Impact of Covid-19 Pandemic Toward Film Festival; Case Study on Jogja Student Film Festival 2020. The Covid-19 pandemic poses a big challenge for the sustainability of film festivals as a space for the distribution and appreciation of student works in Indonesia. The Jogja Student Film Festival (FFPJ), which has been taking place since 2010, faced an extraordinary situation in 2020 when the organization had to transform from an offline format to an online format. This study aims to describe the adaptation process of FFPJ management throughout the pandemic and identify the driving factors for these changes. A qualitative descriptive approach is used with data collection techniques in the form of documentation, structured observations, and interviews with founders, judges, volunteers, and festival participants. The validity of the data is maintained through source triangulation while the analysis is carried out using the management function theory framework (POAC). The results of the study show that strategic adaptation and the use of digital technology allow the sustainability of the festival without permanent sponsors, while still prioritizing aspects of critical literacy and appreciation space for young filmmakers. FFPJ organizers and communities have shown the ability to maintain the existence and regeneration of the student film community even in crisis conditions.Keywords: Student's Film Festival, Covid-19 Pandemic, Existence